Culture Shock: Online Learning in the Covid-19 Pandemic Phase - Sri kuning, Dewi (Penerbit Goodwood, 2021)
Purpose: In this Covid-19 pandemic phase, all teaching and learning process is done by online learning. Online learning is one way the Indonesian government saves the education keep run well because all learning activities are done at home. However, the effect of this activity makes the students shocked. Not only the students but also the parents and the teacher feel the culture shock because of online learning: many advantages and disadvantages to online learning for students. This study gives some solutions for every challenge from online learning in the Covid-19 pandemic. Research methodology: This is a review paper. Results: This article elaborates on the psychological impact of online learning on students. Limitations: This study only tells about the culture shock of online learning for students, teachers, and parents. Contribution: This article can be helpful for school in adding information about the culture shock of online learning and how to solve it.